Understanding and Addressing Challenges Faced by Management Students in Developing English Communication Skills: A Case Study - Raut, Bhakta Bahadur; Dahal, Shanta Bahadur (GS WOW: Wisdom of Worthy Research Journal, 2024)
The article focuses on the challenges faced by Nepalese students in learning English for business communication, particularly in the context of Tribhuvan University's curriculum. The study employs a qualitative approach, collecting primary data through interviews with first and second-year students of the Bachelor of Business Studies (BBS) program at Tribhuvan University. Literature reviews of global context-related articles and books were also conducted to generate ideas and validate the findings. The study highlights issues with the curriculum, teachers, students, and educational institutions that contribute to subpar English language acquisition. The findings suggest that students face numerous obstacles in learning English, including limited exposure to the language, inadequate teaching methods, and lack of motivation. This study contributes to the existing literature by providing insights into the challenges faced by Nepalese students in learning English for business communication, highlighting the need for a more effective and student-centered approach to language acquisition.